The Influence of Neocate in Paediatric Short Bowel Syndrome on PN Weaning - E. De Greef; T. Mahler; A. Janssen; H. Cuypers; G. Veereman-Wauters (Journal of Nutrition and Metabolism)
Clinical management of short bowel syndrome remains a multistage process. Although PN is crucial, early introduction of enteral feeding is mandatory. We describe retrospectively 4 patients with an ultrashort bowel who could be weaned off PN on very short terms after introduction of an amino-acid-based formula (Neocate). Patient 1 had congenital short bowel with 50 cm small bowel and 30 cm colon. He had persistent diarrhoea on a semielementary formula. When Neocate was introduced he could be weaned from PN within 6 months. Patient 2 needed multiple surgical interventions because of NEC at D 27. He maintained 40 cm small bowel and an intact colon and remained PN dependent on semielemental formula. After introducing Neocate, PN could be weaned within 3 months. In the next 2 patients, Neocate was introduced as initial enteral feeding after bowel resection following antenatal midgut volvulus. Patient 3 had 20 cm small bowel and an intact colon. PN was weaned after 2 months. Patient 4 had 9 cm small bowel and an intact colon. PN was weaned after 13 months. In all patients Ileocaecal valve (ICV) was preserved. No consensus is reached on the type of formula to use for short bowel syndrome. Compared to recent data in the literature, the weaning period in these 4 patients was significantly shortened on an aminoacid based formula. The reason for this may lie in the antiallergic properties of this formula. We recommend the use of an amino-acid-based formula to induce earlier weaning of PN.